Surgical techniques in spinal surgery cervical spine : a step by step approach - Ramani, PS (New Delhi : Jaypee Brothers Medical Publishers, 2010)
Se espera que este libro no sólo dará conocimiento, sino infundir mucha confianza deseada en todos los cirujanos de la columna vertebral que siguen este libro paso a paso en dar un mejor servicio a la columna vertebral pacientes enfermos.
Contents Section 1: Basic knowledge of Cervical Spine Section 2: Orientation in the Operation Theater Sectión 3: Techniques of Harvesting bone Gragts From The Iliac Crest And Familiarity With the Use Of Screws And Plates Section 4: Surgical Approaches To Cranio-Vertebral Junction Section 5: Surgical Approaches To Subaxial Anterior Cervical Spine and others more...
Incluye índice
Incluye bibliografía
Keywords: CIRUGÍA DE LA COLUMNA VERTEBRAL; SPINE SURGERY; CIRUGÍA OPERATORIA; TEJIDO NERVIOSO